2018
DOI: 10.1007/s10750-018-3736-3
|View full text |Cite
|
Sign up to set email alerts
|

Size-effect, asymmetry, and small-scale spatial variation in otolith shape of juvenile sole in the Southern North Sea

Abstract: While otolith shape analysis can provide a valuable tool for discriminating between fish populations, factors which may influence otolith shape, such as the effect of size, directional asymmetry in growth, and local environmental conditions, are often unknown. Here, we analyzed differences in otolith shape across three size classes of age-0 common sole Solea solea L. from nursery grounds off the Belgian coast and in the Wadden Sea. Across size classes, form-factor decreased and roundness remained consistently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 43 publications
0
3
0
Order By: Relevance
“…Over all samples, 402 juvenile sole were collected, measured and weighed, and immediately immersed in ice to be sacrificed by hypothermia. In total, 154 juvenile sole were selected for otolith extraction (on average 45% of the juveniles sampled at each sampling location or moment), of which the left otoliths have been used for elemental footprint and shape analysis, published in parallel studies [ 5 , 20 ], while the right-side otoliths were used in this study for daily growth ring analyses. The standard length of the selected individuals was representative for the overall sampled sole cohort per location (average standard length and standard deviation per location highly comparable with the overall averaged standard length and standard deviation (84.76 ± 14.46 mm) of the total fish sampled).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Over all samples, 402 juvenile sole were collected, measured and weighed, and immediately immersed in ice to be sacrificed by hypothermia. In total, 154 juvenile sole were selected for otolith extraction (on average 45% of the juveniles sampled at each sampling location or moment), of which the left otoliths have been used for elemental footprint and shape analysis, published in parallel studies [ 5 , 20 ], while the right-side otoliths were used in this study for daily growth ring analyses. The standard length of the selected individuals was representative for the overall sampled sole cohort per location (average standard length and standard deviation per location highly comparable with the overall averaged standard length and standard deviation (84.76 ± 14.46 mm) of the total fish sampled).…”
Section: Methodsmentioning
confidence: 99%
“…Delerue-Ricard et al [ 5 ] confirmed four natal sources for juvenile sole, based on otolith microchemistry, testifying a certain level of connectivity between spawning and nursery grounds. Chemical signatures associated with the juvenile nursery phase suggest limited movement after settlement and high residency in each nursery along the North Sea coast [ 5 , 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, compared to other natural tracers, otolith shape is relatively cheap and easy to use in routine with a dedicated software. Consequently, otolith shape may suitably complement genetic analyses to capture the various scales at which dispersal processes happen [ 49 , 50 ]. Comparing tracers that integrate information at the ecological and evolutionary time scales may allow to detect spatial population structure and its stability over time [ 51 ].…”
Section: Introductionmentioning
confidence: 99%